2021
DOI: 10.3390/su13158645
|View full text |Cite
|
Sign up to set email alerts
|

Parental Education and Good Child Habits to Encourage Sustainable Littering Behavior

Abstract: Proper habits formed since childhood represent the ideal head start to help keep the environment clean, although this is not a standalone vital factor for a person to dislike littering behavior. The data used in this study were derived from the compilation of primary data. This paper concerns littering behavior of children and presents a survey conducted with 2349 individuals who completed a survey with relevant items and demographic information. The respondents were sampled with a purposive random sampling su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In a recent publication [12], researchers echoed the fact that a proper upbringing of a child potentially represents a great beginning towards developing a good littering behavior. A survey administered by the study recorded responses from 2,349 individuals.…”
Section: A Improving Children's Littering Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent publication [12], researchers echoed the fact that a proper upbringing of a child potentially represents a great beginning towards developing a good littering behavior. A survey administered by the study recorded responses from 2,349 individuals.…”
Section: A Improving Children's Littering Behaviormentioning
confidence: 99%
“…The outcome of the survey showed that lowincome households need support in terms of quality education and disposal facilities while high-income households need support in terms raising awareness on the problems of littering. Though self-initiative and parental guidance constitute a good approach towards improving the littering behavior of children, they are not sufficient [12]. The researchers suggested that future research should explore the effectiveness of religious education on the littering behavior of children.…”
Section: A Improving Children's Littering Behaviormentioning
confidence: 99%
“…Educational and information campaigns can be successful, as shown in the results of studies on toys in Spain [59,60] and on mobile phones in Germany [61]. Such campaigns can even start with very early education by parents [62].…”
Section: Discussionmentioning
confidence: 99%
“…37 This condition is in line with research that indicates that a child learns about right and wrong starting with simple things in everyday life, including keeping the environment clean and throwing rubbish in its place. 38 Other research also reveals that students will treat their environment in accordance with their family's views on the environment. If the interactions within the family are positive, then the emerging attitudes will be positive.…”
Section: Family Quality Of Life (Fqol); Environmental Attitudementioning
confidence: 99%